Hubungan Perilaku Hidup Bersih Dan Sehat (PHBS) Dengan Kejadian Skabies Pada Santri Putra Di Pondok Pesantren Al-Mizan Muhammadiyah Lamongan - Samiyah , Mirrah; Wiliyanarti, Pipit Festi; P, Chlara Yunita (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: The aim of this study is to determine the relationship between Clean and Healthy Living Behavior (PHBS) and the incidence of scabies among male students at Al-Mizan Muhammadiyah Islamic Boarding School in Lamongan. Methods: This research employs a cross-sectional approach with the entire population of male students at Al-Mizan Muhammadiyah Islamic Boarding School in Lamongan. A total of 44 samples were taken using a non-probability sampling technique with total sampling. The independent variable is Clean and Healthy Living Behavior (PHBS), while the dependent variable is scabies. Data collection was conducted using questionnaires and observation sheets, and the data were analyzed using the Chi-Square test. Results: The results indicate that 27 respondents (61.4%) have a moderate level of PHBS, and 27 respondents (61.4%) suffer from scabies. The results show a p-value of 0.001, which is less than 0.05, indicating a significant relationship between Clean and Healthy Living Behavior and the incidence of scabies at Al-Mizan Muhammadiyah Islamic Boarding School in Lamongan. Conclusion: It is concluded that Clean and Healthy Living Behavior can prevent the occurrence of scabies among students.